Identification and Characterization of Two Novel Spliced Genes Located in the orf47-orf46-orf45 Gene Locus of Kaposi's Sarcoma-Associated Herpesvirus - Chang, Pey-Jium (American Society for Microbiology, 2014)
The orf47-orf46-orf45 gene cluster of Kaposi's sarcoma-associated herpesvirus (KSHV) is known to serially encode glycoprotein L (gL), uracil DNA glycosylase, and a viral tegument protein. Here, we identify two novel mRNA variants, orf47/45-A and orf47/45-B, alternatively spliced from a tricistronic orf47-orf46-orf45 mRNA that is expressed in the orf47-orf46-orf45 gene locus during the early stages of viral reactivation. The spliced gene products, ORF47/45-A and ORF47/45-B, consist of only a partial region of gL (ORF47), a unique 7-amino-acid motif, and the complete tegument protein ORF45. Like the ORF45 protein, ORF47/45-A and ORF47/45-B expressed in cells sufficiently activate the phosphorylation of p90 ribosomal S6 kinase (RSK) and extracellular signal-regulated protein kinase (ERK). However, unlike ORF45, both ORF47/45-A and ORF47/45-B contain a signal peptide sequence and are localized at the endoplasmic reticulum (ER). Additionally, we found that ORF47/45-A and ORF47/45-B have an extra function that mediates the upregulation of GRP78, a master regulator of ER homeostasis. The important event regarding GRP78 upregulation can be observed in all tested KSHV-positive cell lines after viral reactivation, and knockdown of GRP78 in cells significantly impairs viral lytic cycle progression, especially at late lytic stages. Compared with some other viral glycoproteins synthesized through the ER, our results strongly implicate that the ORF47/45 proteins may serve as key effectors for controlling GRP78 expression and ER homeostasis in cells. Taken together, our findings provide evidence showing the reciprocal association between the modulation of ER homeostasis and the progression of the KSHV lytic cycle. IMPORTANCE Emerging evidence has shown that several viruses appear to use different strategies to control ER homeostasis for supporting their productive infections. The two parts of this study identify two aspects of the association between the regulation of ER homeostasis and the progression of the KSHV lytic cycle. The first part characterizes the function of two early lytic cycle proteins, ORF47/45-A and ORF47/45-B, on the activation of a major ER chaperone protein, GRP78. In addition to the ability to promote GRP78 upregulation, the ORF47/45 proteins also activate the phosphorylation of RSK and ERK. The second part reveals that upregulation of GRP78 is essential for the progression of the KSHV lytic cycle, especially at late stages. We therefore propose that activation of GRP78 expression by viral proteins at the early lytic stage may aid with the protection of host cells from severe ER stress and may directly involve the assembly or release of virions.